Trialling the 4C framework in an Indian grade 3 mathematics classroom - Rangarajan, Swathi (2017)
This thesis describes an action research carried out in a Grade 3 maths classroom in a low income, English medium school in Mumbai, India. The maths teacher in the study used the 4C model proposed by Do Coyle (2010) as a framework of Content and Language Integrated Learning (CLIL) for teaching maths in English to students whose exposure to English outside the classroom was negligible. The aim of this research was to understand from a teacher’s perspective how the 4C framework contributed to this specific context and how group-work enhanced the 4C framework.